Excursion of bone-patella tendon-bone grafts during the flexion-extension movement in anterior cruciate ligament reconstruction: Comparison between isometric and anatomic reconstruction techniques - Yasuhiro Take; Tatsuo Mae; Ken Nakata; Shigeto Nakagawa; Yuta Tachibana; Konsei Shino (Elsevier, 2015)
Background/objective: The purpose of this study was to elucidate the biomechanical differences between anterior cruciate ligament (ACL) grafts reconstructed by isometric and anatomic reconstruction techniques, based on their length changes. Methods: One hundred and thirty-three knees with primary ACL reconstruction using the bone-patellar tendon-bone (BTB) graft were retrospectively identified. Twenty-two knees and 111 knees underwent isometric round tunnel (IRT) ACL reconstruction and anatomic rectangular tunnel (ART) ACL reconstruction, respectively. Results: After femoral-side fixation of the graft in the surgery, the length change of the graft from 120° flexion to full extension was measured by using an isometric positioner at the tibial side. Both reconstructive techniques showed little length change from 120° to ∼20° of flexion, followed by elongation of the graft, until full extension. The amount of length change of the grafts was 1.0 ± 0.7 mm with the IRT technique, and 3.4 ± 0.9 mm with the ART technique. These findings were significantly different, based on the Mann-Whitney U test (p < 0.001). Conclusion: The native ACL has an intrinsic length change of 3-6 mm, and therefore the ART technique may more closely replicate the biomechanical function of the native ACL.